Nanoformulation improves antitumor efficacy of MAOI immune checkpoint blockade therapy without causing aggression-related side effects - Brown, James; Li, Zhe; Wang, Xi; Kim, Yu Jeong; Wang, Yu-Chen; Zuo, Yanning; Hong, Weizhe; Wang, Pin; Li, Bo; Yang, Lili (Frontiers in Pharmacology, 2022)
MAOIs, a well-established antidepressant that operate through the inhibition of monoamine oxidase to increase available serotonin, have recently been identified as a surprisingly effective candidate for the circumvention of tumor-induced immune suppression due to their abilities to enhance antitumor T cell activity through autocrine serotonin signaling and depolarize alternatively activated tumor-associated macrophages through a reduction in reactive oxygen species production. However, this impressive class of antidepressants-turned-cancer-drugs is associated with many negative behavioral side effects that result from the neuropharmacology of the drugs. In this study, we investigated the possibility of circumventing these neurological side effects while simultaneously improving antitumor activity by establishing crosslinked multilamellar liposomal vesicles (cMLVs) containing the MAOI phenelzine that do not infiltrate the brain. Our results showed that cMLV-phe increases antitumor efficacy in a B16-OVA mouse melanoma model compared to treatment with free phenelzine. We also found that nanoformulation resulted in the complete elimination of MAOI-related aggression. These findings suggest a promising direction for the future of MAOIs repurposed for cancer immunotherapies.